The effects of logical–mathematical intelligence and growth mindset on students’ numeracy and academic achievement - Munzayanah, Nurul; Usodo, Budi; Fitriana, Laila; Pramesti, Getut (Universitas Hamzanwadi, 2026)
Numeracy skills and academic achievement are key indicators of student educational success and are influenced by both cognitive and non-cognitive factors. However, previous studies have often examined logical–mathematical intelligence and a growth mindset separately, so empirical evidence on their combined role in influencing numeracy skills and academic achievement remains limited. Therefore, this study investigates the influence of logical–mathematical intelligence and growth mindset, both independently and interactively, on students’ numeracy skills and academic achievement. This study employed an exploratory quantitative factorial design using a two-way Multivariate Analysis of Variance (MANOVA) approach, involving a small sample of 30 ninth-grade students from a public junior high school in Jepara, Indonesia, which requires cautious interpretation of the findings. The results indicate that logical–mathematical intelligence has a significant effect on students’ numeracy skills (p < .001), while growth mindset significantly affects students’ academic achievement (p = .02). However, there is no significant interaction between logical–mathematical intelligence and growth mindset on both dependent variables (p = .937). Based on the results, these findings indicate that logical–mathematical intelligence and growth mindset are independently associated with different learning outcomes, rather than exerting a combined or interactive effect.